Classification of middle- and long-distance runners based on their competition results - Iljukov, S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The scientific literature lacks consensus on classification of middle- and long-distance runners. Many terms are used to describe the proficiency level of athletes. This creates situations where the sample studied may not represent the target population and could produce misleading results. Thus, we present an approach for a data-driven classification of middle- and long-distance runners according to their competition results.